More Thoughts on the Physician's Constitutional Role in Abortion and Related Choices - Susan Frelich Appleton (Washington University Law Quarterly, 1988)
A few years ago, I advanced the hypothesis that the true focus of the Supreme Court's decisions protecting abortion has been the physician not the patient, the pregnant woman, nor the individual seeking to assert what the Court calls "the right to privacy." I explained how the Court's preoccupation with medical standards in resolving constitutional questions about abortion and the Court's frequent portrayal of the physician as the ultimate decisionmaker in every abortion choice create a tension that peaks in judicial reviews of state efforts to regulate informed consent to abortion. Now, some years later, I look again at the main idea of my earlier work, that the physician is the real centerpiece of the Supreme Court's abortion doctrine. This time I consider two particular questions: First, have the courts continued to elevate the physician at the expense of the abortion patient in the recent assessments of "informed consent" regulations and in challenges to rules prohibiting abortion counseling, the newest restriction on the abortion patient's dialogue with her doctor? Second, despite its other difficulties, how might the doctor-focused regime contribute to an analysis of recent outgrowths of the abortion question, including fetal tissue transplants (the subject of John Robertson's and Nicholas Terry's papers), "abortion pills," forced Caesarians and other maternal-fetal conflicts, and modern reproductive technology?
Keywords: Physicians; Informed consent (Medical law)